2008
DOI: 10.1007/s12237-008-9104-1
|View full text |Cite
|
Sign up to set email alerts
|

Net Ecosystem Metabolism and Nonconservative Fluxes of Organic Matter in a Tropical Mangrove Estuary, Piauí River (NE of Brazil)

Abstract: Net ecosystem metabolism (NEM) was measured in the Piauí River estuary, NE Brazil. A mass balance of C, N, and P was used to infer its sources and sinks. Dissolved inorganic carbon (DIC) concentrations and fluxes were measured over a year along this mangrove dominated estuary. DIC concentrations were high in all estuarine sections, particularly at the fluvial end member at the beginning of the rainy season. Carbon dioxide concentrations in the entire estuary were supersaturated throughout the year and highest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 40 publications
3
16
0
5
Order By: Relevance
“…Survey data from the lower estuary during July 2009 were excluded due to an incongruent transect route. (Figures 2 and 3) [Frankignoulle et al, 1998;Cai et al, 1999;de la Paz et al, 2007;Zhai et al, 2007;Guo et al, 2009;Souza et al, 2009]. In the spring and summer, conditions in the wind-driven NRE were most similar to those seasonally observed by Koné et al [2009] in the microtidal Aby Lagoon, Ivory Coast.…”
Section: Inorganic C Dynamics In the Nresupporting
confidence: 55%
“…Survey data from the lower estuary during July 2009 were excluded due to an incongruent transect route. (Figures 2 and 3) [Frankignoulle et al, 1998;Cai et al, 1999;de la Paz et al, 2007;Zhai et al, 2007;Guo et al, 2009;Souza et al, 2009]. In the spring and summer, conditions in the wind-driven NRE were most similar to those seasonally observed by Koné et al [2009] in the microtidal Aby Lagoon, Ivory Coast.…”
Section: Inorganic C Dynamics In the Nresupporting
confidence: 55%
“…In Brazil, most previous studies have concerned riverdominated estuaries, especially along the northern and northeastern coast, which all behave as CO 2 sources (Souza et al, 2009;Araujo et al, 2014;. In contrast to Guanabara Bay, highest CO 2 fluxes correspond to denser population in the watersheds of these net heterotrophic systems .…”
Section: Discussionmentioning
confidence: 99%
“…However, the limited number of available studies suggest that tropical estuaries are generally sources of CO 2 to the atmosphere (Souza et al, 2009;Sarma et al, 2012;Araujo et al, 2014), with the exception of one lagoon (Koné et al, 2009). Also, most studies are potentially biased by the lack of information on the diurnal variations in CO 2 , which corresponds to a crucial component of mass balance calculations (Borges and Frankignoulle, 1999;Zhang et al, 2013;Maher et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study [12] reported an efflux of 13 mol CO 2 m −2 ·yr −1 for a tropical estuary (the Piauí estuary, Brazil, latitude 10˚S). As indicated by [6], the current calculation is based on a very limited data set from subtropical and tropical regions.…”
Section: Introductionmentioning
confidence: 99%